A fused mixed-methods approach to thematic analysis of personal networks: Two case studies of caregiver support networks. (June 2021) - Yousefi Nooraie, Reza; Thompson, Bronwyn; D'Silva, Chelsea; Zenlea, Ian; Tabatabaee, Maryam; Mohammad Aghaei, Ardavan
Abstract: Thematic analysis of personal networks involves identifying regularities in network structure and content, and grouping networks into types/clusters, to allow for a holistic understanding of social complexities. We propose an inductive approach to network thematic analysis, applying the learnings from qualitative coding, fused mixed-methods analysis, and typology development. It involves framing (changing focus by magnifying, aggregating, and graphical configuration), pattern detection (identification of underlying dimensions, sorting, and clustering), labeling, and triangulating (confirmation and fine-tuning using quantitative and qualitative approaches); applied repeatedly and emergently. We describe this approach utilized in two cases of studying support networks of caregivers.